Reduced evolutionary potential of a frugivorous bird species in fragmented forests - Assis, Ana Paula A.; Galetti, Mauro; Maia, Kate P.; Guimarães, Paulo R. (Frontiers in Ecology and Evolution, 2022)
Morphological attributes are important in determining the success of ecological interactions, such as the interactions between fleshy fruited plants and their seed dispersers. Morphological traits can present high levels of intraspecific variation both within and across populations. Such variation will not only mediate which interactions can be established locally but also the potential for populations to respond to perturbations and selective pressure. Here, we investigated patterns of morphological variation (body weight and beaks’ traits) among different populations of blue manakin (Chiroxiphia caudata), in the highly fragmented Atlantic Forest, Brazil, both in terms of mean trait values - that might mediate interactions locally - and in their habitat-level variation which influences their evolutionary potential. Using metrics of evolutionary potential derived from quantitative genetics theory, we hypothesized that ecological stress would lead to a decline in the overall evolutionary potential in manakin populations. We found that populations differ slightly in their mean morphological attributes, with the exception of a population that occurs in temperate Araucaria forests. Nevertheless, we found a striking difference in the evolutionary potential of populations from different vegetation types. Specifically, populations that occur in ecological stress areas, Araucaria forests, and forest fragments immersed in savanna presented a smaller overall and conditional evolvability, suggesting their lower ability to respond in the direction of selection. This pattern might have important implications for the role of this species as seed disperser, as populations under stress may lack morphological variation (and covariation) that can be important to allow a given population to disperse seeds of multiple types of fruits. Moreover, a smaller evolvability might impact the potential of these populations to persist and perform their ecosystem services in face of environmental changes.